Autoavaliação de professores dos anos iniciais: um olhar para a construção do amadurecimento pedagógico - Ferraz, Raquel Brum (Universidade do Vale do Rio dos Sinos, 2023)
This study aims to investigate the main bases underlying the self-assessment of Early Years teachers, with regard to the critical analysis of their pedagogical practice, personal evolution and professional excellence in the context of teaching-learning. The focus of this research is on the teaching staff of Colégio Farroupilha, in Porto Alegre (RS), made up of a total of sixty teachers. Given the unfeasibility of fully addressing this population, the selection of a representative sample became an appropriate methodological approach, guided by criteria of convenience and randomness. The present study is justified by the interest of verifying whether the Early Years teacher at Colégio Farroupilha, in the city of Porto Alegre, reflects on his professional maturity and understands how the self-evaluation process takes place regarding the quality of teaching of the institution's educators. The interest in delving deeper into this topic arose through the concerns that the author carries in her professional journey. The study on this topic is considered relevant, as is the importance of self-assessment for aligning expectations and also for recognizing the journey taken. The research adopted a descriptive qualitative approach, using an individual questionnaire as a data collection instrument, applied to twelve teachers at the institution, and complemented by in-depth interviews, conducted with six teachers at the school. The key question that guided the study was: “Do you realize that the feedback provided by your educational institution promotes self-evaluation in your teaching practice and has impacted your professional development? Comment.” Through this inquiry, the final results of the study emerged and were subjected to categorization, according to the methodological scheme proposed by Laurence Bardin. This categorization process was conceived as an interactive and dynamic system, allowing the reevaluation and redefinition of categories as new data was collected and subjected to analysis. The central purpose of this study was to illuminate the relevance of institutional feedback as a tool that promotes internal reflection on the part of teachers, thus stimulating the continuous improvement of their professional practices. The five objectives proposed in this work were completed and the results obtained offer a deeper understanding of teachers' perceptions in relation to these principles, contributing significantly to a more comprehensive understanding of the processes involved in the training and constant development of teaching staff who work in Initial years of teaching. The authors who came closest to the way the author understands the evaluation and form cited throughout this dissertation were Alcaraz (2007), Perrenoud (2000), Tardif (2000), Nieto (2003) and Hadgi (2001).
Keywords: Autoavaliação; Aprimoramento pedagógico; Professores; Anos iniciais; Feedback; Self-assessment; Pedagogical improvement; Teachers; Initial years; ACCNPQ::Ciências Humanas::Educação